GEOSPATIAL ANALYSIS OF HEALTH CARE RESOURCE ALLOCATION IN KARUR DISTRICT: INSIGHTS FROM GIS - Umasankar; R. Vijaya; V. Saravanabavan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Primary Health Care System is essential in delivering critical services such as maternal and child health care, family planning, immunization, provision of essential drugs, and promotion of nutrition and sanitation. In rural areas, effective implementation of primary health care is often hampered by challenges such as inadequate health manpower, entrenched traditional cultural practices, and the dominance of indigenous medicine systems. Additionally, the concentration of health services and personnel in urban areas exacerbates the disparity in healthcare accessibility for rural populations. This study aims to address these disparities by analyzing the spatial distribution of primary health care resources in Karur District current distribution and accessibility of PHCs to health resource allocation. This study addresses these issues by employing Geographical Information System (GIS) techniques to analyze the spatial distribution of primary health care resources in Karur District. By applying Thiessen polygon analysis, we delineate the service areas of Primary Health Centres (PHCs) and evaluate the availability of essential resources, including doctors, staff nurses, auxiliary nurse midwives, and hospital beds. The insights gained from this geospatial analysis highlight the gaps in healthcare provision and offer recommendations for optimizing the allocation of health resources to improve accessibility and service delivery in rural areas.